Leaf area index of potato crop under three nitrogen fertilization treatments (2017)
Nitrogen fertilization has considerable effects on growth and yield of the potato crop. Additionally, leaf expansion is one of the most important growth parameters that can be used to optimize the management of agroecological resources. We evaluated the effect of nitrogen fertilization on the leaf area index (LAI) of the potato crop during different phenological stages by two different methods. Experimental plots were stablished in a randomized block design with three replicates per fertilization treatment: no nitrogen supply (0-N), 133 Kg N ha-1 (133-N), and 400 Kg N ha-1 (400-N), using the Granola variety, at the Andes region, Mérida city, Venezuela. We measured leaf area at the main phenological stages of the crop using a plant canopy analyzer. LAI showed significant differences among treatments and phenological stages, except during the emergence stage. The maximum LAI values were obtained ca. 55 days after emergence: 400-N (1.42 ± 0.16) 133-N (0.92 ± 0.21) 0-N (0.34 ± 0.08). We showed that nitrogen fertilization had a significant effect on the development of LAI in the potato crop along its different phenological stages.